2014
DOI: 10.1002/ajh.23802
|View full text |Cite
|
Sign up to set email alerts
|

Donor NK cell licensing in control of malignancy in hematopoietic stem cell transplant recipients

Abstract: on behalf of the Polish Donor-Recipient Matching Study Group Among cancers treated with allogeneic hematopoietic stem-cell transplantation (HSCT), some are sensitive to natural killer (NK) cell reactivity, described as the "missing self" recognition effect. However, this model disregarded the NK cell licensing effect, which highly increases the NK cell reactivity against tumor and is dependent on the coexpression of inhibitory killer cell immunoglobulin-like receptor (iKIR) and its corresponding HLA Class I li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…In a mouse model, Yokoyama and Kim (2006) demonstrated that NK cells are regulated by the host class I MHC molecules. Nowak et al (2014) also revealed dramatic reductions in overall survival, progression-free survival and time to progression among patients with malignant disease lacking cognate HLA ligands for donor inhibitory KIRs involved in NK cell licensing following unrelated transplantation, further confirming the key roles of class I ligands for donor inhibitory KIRs in recipients in NK cell licensing post-transplantation. Boudreau et al (2016) recently demonstrated that NK cell reactivity increased or decreased when HLA was acquired from neighbouring cells or was silenced in educated cells, respectively.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In a mouse model, Yokoyama and Kim (2006) demonstrated that NK cells are regulated by the host class I MHC molecules. Nowak et al (2014) also revealed dramatic reductions in overall survival, progression-free survival and time to progression among patients with malignant disease lacking cognate HLA ligands for donor inhibitory KIRs involved in NK cell licensing following unrelated transplantation, further confirming the key roles of class I ligands for donor inhibitory KIRs in recipients in NK cell licensing post-transplantation. Boudreau et al (2016) recently demonstrated that NK cell reactivity increased or decreased when HLA was acquired from neighbouring cells or was silenced in educated cells, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…In the setting of CBT, Sekine et al (2016) reported that HLA-C1/x patients should receive an HLA-C1-KIR2DL2/L3/S2 cord blood graft, while HLA-C2/C2 patients may benefit from an HLA-C2-KIR2DL1/S1 graft. Nowak et al (2014) also revealed dramatic reductions in overall survival, progression-free survival and time to progression among patients with malignant disease lacking cognate HLA ligands for donor inhibitory KIRs involved in NK cell licensing following unrelated transplantation, further confirming the key roles of class I ligands for donor inhibitory KIRs in recipients in NK cell licensing post-transplantation. In accordance with their report, our findings have indicated that HLA-C1/C1 patients should receive an HLA-C1C1 haplograft, while HLA-C1C2 patients should receive an HLA-C1C2 haplo-graft; in addition, HLA-Bw4/X patients should receive an HLA-Bw4X haplo-graft post haplo-SCT.…”
Section: Discussionmentioning
confidence: 67%
“…The binding of HLA to a cognate inhibitory KIR has a dual inhibitory and educational function (Kim et al, ; Long et al, ). While NK cell activation may be the result of negative recognition (missing ligand recognition) by inhibitory KIRs, NK cell education or licensing depends on the positive binding of KIR to cognate HLA and hence “arming” NK cells (Kim et al, ; Nowak et al, ). To become licensed, NK cells distinguish between cognate and nonbinding HLAs using KIR.…”
Section: Selection Of Hla Class I Motifs Involved In Kir Bindingmentioning
confidence: 99%
“…Within the frames of recognition, HLA class I molecules are evolutionally and functionally selected in close correlation with the specificity of the KIR genes (Guinan et al, ; Parham, ; Parham, Norman, Abi‐Rached, & Guethlein, ). In HSC transplant patients, increasing evidence shows that unlike KIR ligand mismatch the cognate HLA:KIR pairings are of primary clinical importance for cancer immunosurveillance, lower relapse incidence and better survival (Gaafar et al, ; Graczyk‐Pol et al, ; Hoseinian et al, ; Nowak et al, , ; Rogatko‐Koroś et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of donor HLA ligand for cognate inhibitory KIR has been associated with adverse survival due to disease progression after URD HCT 20 .…”
Section: Introductionmentioning
confidence: 99%